Roles of Dynamic and Thermodynamic Processes in Regulating the Decay Paces of El Niño Events - Lee, Chung-Wei; Sui, Chung-Hsiung; Li, Tim (Journal of climate, 2023)
Most El Niño events decay after a peak in boreal winter, but some persist and strengthen again in the following year. Several mechanisms for regulating its decay pace have been proposed; however, their relative contributions have not been thoroughly examined yet. By analyzing the fast-decaying and persistent types of the events in a 1200-yr coupled simulation, we quantify the key dynamic and thermodynamic processes in the decaying spring that are critical to determining the decay pace of El Niño. The zonal advection due to upwelling Kelvin wave accounts for twice as much the cooling difference as evaporation or meridional advection does. The upwelling Kelvin wave is much stronger in the fast-decaying events than the others, and its strength is equally attributed to the reflected equatorial Rossby wave and the equatorial easterly wind forcing over the western Pacific in the preceding 2–3 months. Relative to the fast-decaying events, the evaporative cooling is weaker but the meridional warm advection is stronger in the persistent events. The former is due to more meridionally asymmetric wind and sea surface temperature anomalies (SSTA) signaling positive Pacific meridional mode. The latter results from the advection of equatorial warm SSTA by climatological divergent flow, and the warmer SSTA persists from the mature stage subject to weaker cloud-radiative cooling in response to the central-Pacific-type SSTA distribution in the persistent events relative to the fast-decaying events. Our result consolidates the existing knowledge and provides a more comprehensive and physical pathway for the causality of El Niño’s diverse duration.